INNOVATIVE STRATEGIES FOR INCORPORATING DIGITAL TECHNOLOGIES INTO HIGHER MUSIC AND ARTS EDUCATION - Inna PASHCHENKO; Natalia SEHEDA; Svitlana TERESHCHENKO; Liliia CHERVONSKA (Studia Universitatis Babeş-Bolyai. Musica)
The modern educational system, responding to the needs of society, is actively transforming and integrating innovative approaches, among which digital technologies occupy a special place. The introduction of digital tools allows us to go beyond traditional learning and create an innovative educational environment focused on developing creativity and critical thinking. In the context of martial law in Ukraine and after the coronavirus crisis, digital technologies have become the basis for organizing the educational process, ensuring effective remote interaction between teachers and students. The study aims to comprehensively assess the impact of digital tools on the quality of training in higher art (music) education and to determine the potential of digital technologies for transforming modern pedagogical practices. The research used systematic and comparative approaches to study the theory and practice of integrating digital technologies into higher art (music) education. The article analyses the transformation processes in music and music education caused by the digitalization of society. It is proven that digital technologies are reforming music education, making it more open, dynamic and effective. This contributes to the development of the global music community and opens up new opportunities for creative expression. It is found that the use of artificial intelligence in the field of higher art (music) education is one of the most promising areas of modern pedagogical research. The application of virtual reality as a tool for interactive music teaching and simulation of concert performances is analyzed. It has been proved that modern artistic higher education is increasingly moving away from passive knowledge acquisition and towards the active development of each student's creative potential.